Z którą teologią polityczną mamy do czynienia? Oceniając genealogię teologii politycznej i wypatrując jej przyszłości - Colby Dickinson (Praktyka Teoretyczna, 2015)
In this essay, I examine Michel Foucault’s political contrast between the theological domains of the pastoral and the mystical, in order to note his focus on how necessity and providence are founding and legitimizing concepts of the State. Through this process I develop an analysis of how Foucault, in his critique of the historical uses of theology as a tool of pastoral power, actually points toward another form of political theology than Carl Schmitt’s. My contention is that we begin to see another “type” of political theology appear in the writings of Giorgio Agamben, who follows Christian traditions much more closely than Foucault. The re-formulation of political theology within Agamben’s work, I argue, has tremendous significance for the field as a whole and is much in need of further elaboration, a task toward which this essay only points.